Cognitive processing of moral and social judgements: A comparison of offenders, students, and control participants. Issue 2 (February 2015) - Lahat, Ayelet; Gummerum, Michaela; Mackay, Lorna; Hanoch, Yaniv
Examining cognitive processes related to offenders' moral and social judgements is important in order to better understand their criminal behaviour. In the present study, 30 offenders, 30 students, and 24 control participants were administered the moral-conventional judgements computer task, which requires responding under strict time constraints. Participants read scenarios and were asked to judge whether the act was acceptable or unacceptable when rules were either assumed or removed. Additionally, participants completed an executive function (EF) task in order to examine the relation between EF and moral and social judgements. The findings revealed that, as expected, controls and students had faster reaction times (RTs) and a higher percentage of normative judgements than offenders. Additionally, offenders had a low percentage of normative judgements, particularly in the conventional rule removed condition. Finally, RTs of moral and conventional judgements in most conditions were related to EF among students but not controls or offenders. We conclude that offenders, as compared to controls and students, may rely more on rule-oriented responding and may rely less on EF when making moral and social judgements.